2013
DOI: 10.11648/j.ijmsa.20130205.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mechanical Properties and Absorption Behaviour of Coconut Shell Powder-Epoxy Composites

Abstract: Abstract:The present paper reports to develop a polymer matrix composite (Epoxy-resin) using coconut shell powder (CSP) in different particle size and reinforcing in different volume and evaluate its tensile strength, flexural property and hydrophilic behavior along with engineering application of resulting composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…The density of the composite from this study is about the same as the density of coconut shell composites from previous studies by Singh et al [ 15 ] and Bhaskar et al [ 39 ]. Comparing to the rice straw composite [ 37 ], the density of the coconut shell composite is much higher than the density of the rice straw composite.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The density of the composite from this study is about the same as the density of coconut shell composites from previous studies by Singh et al [ 15 ] and Bhaskar et al [ 39 ]. Comparing to the rice straw composite [ 37 ], the density of the coconut shell composite is much higher than the density of the rice straw composite.…”
Section: Resultssupporting
confidence: 77%
“…Singh et al used micro size coconut shell particles to form a composite with the epoxy. Their report showed that the microparticles enhancement improved the flexural strength and density of the composite [ 15 ]. Somashekhar et al combined coconut shell powder and tamarind shell powder to form a composite by using the epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…APPLICATIONS OF COCONUT FIBER Alok Singh et al [1] found that the mechanical properties viz. density, tensile strength and flexural strength of CSP epoxy composite material is greatly influenced by the CSP filled volume fraction.…”
Section: IVmentioning
confidence: 99%
“…Alok Singh et al [1] describes that the coconut shells are available in abundance in tropical countries as a waste product after consumption of coconut water and meat. Such abundance can fulfil the demand of filler based composites while reducing waste.…”
Section: Introductionmentioning
confidence: 99%
“…Imoisili et al had study the concentration effect of coconut shell ash (CSA) on the tensile properties of polyester composite was investigated. Five filler concentrations (5 to 25 weight %) were fabricated, Results were obtained for each of the tensile strength, elastic modulus, and micro-Hardness of the composite increases with increase in filler concentration, while percentage elongation and load at break decreases with increase in filler concentration [4].…”
Section: Introductionmentioning
confidence: 99%